The Antarctic tourism in foreign publications for 1991-2005 - A. P. Fedchuk (Ukrainian Antarctic Journal, 2005)
The review of the foreign English-language scientific literature on the Antarctic tourism problematic for 1991-2005 is made. On the basis analysis of volumes and dynamics of an output publications, wavy interest of scientific community to the specified problematic is revealed: peak of the first wave - 1994-1996, the second - 2002. It is structured 410 records of a bibliographic database for the allocated period with the help of bibliometrics analysis methods. It is shown, that the greatest numbers of sources are submitted at the Antarctic Treaty Consultative Meetings. According to the basic aspects of a problematic the 12 researches directions are allocated. The volume and dynamics growth of researches on ecological aspects of tourism development is coordinated with the tendency of the general ecologization scientific researches in Antarctic Region. At the same time, it is revealed the differences in structure publications on aspects of the Antarctic tourism and  Antarctic science. It is established, that legal regulation questions of tourist activity and its conformity to the basic documents of Antarctic Treaty System are given more than 20 % of publications. The significant layer of unfinished questions is discovered and tendencies of researches directions diversification are planned. The value of constructive character scientific-practical development with a well-defined geographical component is shown and its significance for sites management plans composition and improvement the regional tourist policy are described. Results of the researches connected with the area of scientific interests of Ukrainian in Antarctic are separately covered.